A highly activated and integrated nanoscale interlayer of cathodes in low-temperature solid oxide fuel cells via precursor-solution electrospray method. (15th February 2019) - Shin, Sung Soo; Kim, Jeong Hun; Li, Guangmin; Lee, Seung Yong; Son, Ji-Won; Kim, Hyoungchul; Choi, Mansoo
Abstract: This study demonstrates the fabrication of a highly activated and integrated nanoscale interlayer of cathodes in low-temperature solid oxide fuel cells (SOFCs) using the precursor-solution electrospray method. Uniform, crack-free La0.6 Sr0.4 CoO3− δ (LSC) and LSC-CeO2 thin-film layers are fabricated by using optimized precursor-solution electrospray and sintering conditions. The LSC–CeO2 composite layer served as a nanoscale-cathode-functional layer (nCFL) by suppressing grain growth and increasing the number of triple-phase boundaries. The LSC nanoscale-adhesive layer (nAL) played a limited role as an adhesive layer due to a large amount of grain growth and limited triple-phase boundaries. Low-temperature SOFCs with the nAL and nCFL nanoscale interlayers showed maximum power densities of ∼1.108 and 1.150 W cm −2 at 650 °C, which were ∼13% and 18% higher, respectively, than those of a reference cell without nanoscale interlayers. Graphical abstract: Image 1 Highlights: A modified precursor-solution electrospray was used for forming nanoscale layer. This structure was applied as a highly activated and integrated interlayer of SOFC. The composite interlayer of LSC and GDC provides better performance and stability. Interlayer assisted cells resulted in peak power density of ∼1.150 W cm −2  at 650 °C.